Using deep learning to analyze the psychological effects of COVID-19 - Almeqren, Monira Abdulrahman; Almuqren, Latifah; Alhayan, Fatimah; Cristea, Alexandra I.; Pennington, Diane (Frontiers in Psychology, 2023)
The world is currently facing significant challenges due to the COVID-19 crisis. Beyond the health effects of the pandemic, there are social and economic effects. Social media generates a significant amount of data, which research can use to provide mental health and psychological solutions. Our research aims to mine Saudi Arabian tweets using a deep learning model to analyze the psychological effects of COVID-19 in Saudi Arabia, and to propose appropriate solutions to overcome these effects. The results of this study can be used to formulate solutions to increase psychological resiliency. by the Saudi Ministry of Health and members of the research community. Our corpus includes 955 Arabic tweets and Python script is used to search for real-time tweets that mention COVID-19, using hashtags to monitor the latest sentiments of the Saudi community, starting in April 2020. The corpus and the lexicon will be freely released to the research community.